(untitled) (Research, Society and Development, 2022)
Organ donation brings immeasurable benefits to the recipient, being sometimes the only alternative for certain diseases. Brazil, in turn, has the largest public transplant system in the world and had been showing an increase in the rate of donors until the Covid-19 pandemic. However, it is clear that the country is able to further improve the numbers of transplants performed and health education on the subject, when well implemented and disseminated, positively interferes in the process. From this, the objective was to carry out an integrative review of the literature to understand the perception of undergraduate students in the health area about organ donation in Brazil. The scientific databases used were PubMED, LILACS, BDENF and SciELO, from which articles were selected from the keywords and their corresponding words in English “estudantes/students” and “doação de órgãos/organ donation”, with the boolean operator “AND” during the period from November 2021 to January 2022. The search resulted in 426 articles, 380 in PubMED, 28 in LILACS, 10 in BDENF and 8 in SciELO, and the final selection consisted of 14 publications. From the analysis of the selected articles, it is understood that students in the health areas have a positive view of organ and tissue donation and intend to donate their organs, despite the evidence of knowledge gaps and sociocultural stigmas that surround the theme.